Academic Senate Minutes 2008-10-02 - Academic Senate:::::::::
Chair Report. Agenda Approved. Minutes of 9/25/08 approved. End of Year Reports from SAC and the GE subcommittee. More on Robert's Rules. President report. Chair-Elect report. Statewide Senator report. CFA report. Resolution opposing Proposition 8, first reading waived and approved by secret ballot. First WASC discussion on the Mission of the University.